Seismic Evaluation of Graha 10 Nopember Building Using Indonesian Earthquake Hazard Deaggregation Map 2022 - Aini, Khusniatul; Habieb, Ahmad B. Habieb Basshofi (Institut Teknologi Sepuluh Nopember, 2025)
The occurrence of large-scale earthquakes in Indonesia is still one of the phenomena that often occurs, this can cause damage to buildings, so applying standardization of earthquake-resistant buildings during construction is necessary. This study review was carried out on Graha Sepuluh Nopember building using evaluation method to earthquake-resistant buildings regulated in Indonesian Earthquake Hazard Deaggregation Map (Pusgen, 2022). The model was evaluated using nonlinear time history analysis in order to obtain behavior in post-elastic conditions. The result of this research uses parameters of displacement and plastic hinge, indicates that the building has immediate occupancy performance level means that the building structure is safe, structural failure is not significantly damaged and can be used again immediately.Keywords Nonlinear time history analysis, Indonesian earthquake hazard deaggregation map, earthquake-resistant building, ground motion